A Flexible Strategy for Modular Synthesis of Curcuminoid‐BF2/Curcuminoid Pairs and Their Comparative Antiproliferative Activity in Human Cancer Cell Lines. (21st January 2020) - Abonia, Rodrigo; Laali, Kenneth K.; Raja Somu, Dawn; Bunge, Scott D.; Wang, Esther C.
Abstract: A facile protocol that enables synthetic interconversion of CUR‐BF2 and CUR compounds is described that significantly widens the preparative scope of curcuminoids, providing access to larger libraries of compounds, thus enabling comparative antiproliferative and apoptotic study of a larger library of synthetic analogs in cancer cell lines. Abstract : Curcumin's resurgence : We developed a flexible protocol that enables synthetic curcuminoid‐BF2 /curcuminoid pairs to be interconverted. This widens their synthetic scope, allowing access to more diverse libraries of CUR‐BF2 /CUR pairs for antiproliferative and apoptotic studies in cancer cell lines.